Prognostic impact of microsatellite instability in gastric cancer - Cesar Zepeda-Najar (Termedia Publishing House, 2021)
Gastric cancer is a common and deadly cancer. Several factors are associated with its prognosis; however, controversy exists about the role of microsatellite instability (MSI). We aimed to determine the 5-year overall survival (OS) of MSI in gastric adenocarcinoma. A cross-sectional study was carried out on gastric adenocarcinoma in clinical stages I to III treated with D2 gastrectomy between 2010–2013. MSI was demonstrated by immunohistochemistry. We performed a survival analysis comparing cases with and without MSI. From 102 cases, 9.8% showed MSI. The median age was 63 years (range 33–91 years), and 57.8% were men. The more prevalent site of occurrence was the antrum (46.1%), 78.5% of the cases presented in stage III, 47.1% were of the diffuse type, 45.1% were of an intestinal type, and 7.8% were mixed. MSI cases were associated with lower clinical stages (stages I–II) and with better 5-year OS (100 vs. 47 months, p = 0.017). In a multivariate analysis, MSI was independently associated with better survival (HR = 0.209, 95% CI: 0.046–0.945, p = 0.042). MSI gastric cancers presented in early clinical stages and had favourable prognosis compared with non-MSI cancers.